Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11214-010-9690-7
|View full text |Cite
|
Sign up to set email alerts
|

Low Latitude Ionospheric Electrodynamics

Abstract: The low latitude ionosphere is strongly affected by several highly variable electrodynamic processes. Over the last two decades ground-based and satellite measurements and global numerical models have been extensively used to study the longitude-dependent climatology of low latitude electric fields and currents. These electrodynamic processes and their ionospheric effects exhibit large ranges of temporal and spatial variations during both geomagnetic quiet and disturbed conditions. Numerous recent studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 122 publications
4
94
0
Order By: Relevance
“…6). This further supports our suggestion that periodic variations reported in this study at least partially can be related to lunar tides that are consistently present in the atmosphere and become strongly enhanced 128 X. H. Mo et al: Quasi-16-day periodic meridional movement of the EIA during SSW events (Pedatella and Forbes, 2010;Fejer et al, 2010;Fejer, 2011;Yamazaki, 2013). Mukhtarov et al (2010) used SABER/TIMED temperature and solar wind velocity data to identify a zonally symmetric oscillation with 14-day period in ionosphere that was considered to be of solar origin and a 18-day westwards propagating planetary wave with zonal wavenumber 1 in stratosphere and MLT region at 50 • N. Vineeth et al (2007) showed the obvious quasi-16-day periodic variation in equatorial mesopause temperature observed in the Indian sector during 2005/2006 SSW event, and their following studies showed that the obvious quasi-16-day periodic planetary wave in tropic stratosphere occurred about 60 days ahead of the 2005/2006 major SSW (Vineeth et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…6). This further supports our suggestion that periodic variations reported in this study at least partially can be related to lunar tides that are consistently present in the atmosphere and become strongly enhanced 128 X. H. Mo et al: Quasi-16-day periodic meridional movement of the EIA during SSW events (Pedatella and Forbes, 2010;Fejer et al, 2010;Fejer, 2011;Yamazaki, 2013). Mukhtarov et al (2010) used SABER/TIMED temperature and solar wind velocity data to identify a zonally symmetric oscillation with 14-day period in ionosphere that was considered to be of solar origin and a 18-day westwards propagating planetary wave with zonal wavenumber 1 in stratosphere and MLT region at 50 • N. Vineeth et al (2007) showed the obvious quasi-16-day periodic variation in equatorial mesopause temperature observed in the Indian sector during 2005/2006 SSW event, and their following studies showed that the obvious quasi-16-day periodic planetary wave in tropic stratosphere occurred about 60 days ahead of the 2005/2006 major SSW (Vineeth et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, there is a possibility of efficient driving of the low-to middle-latitude ionosphere by HSSs through moderate PPEFs. Another explanation is that electric field and current perturbations cause increases in magnetospheric convection and move the nighttime shielding layer equatorward, causing temporary undershielding and dawn-dusk middle-and low-latitude electric fields (see a review by Fejer, 2011). We would like to note that PPEF effects are LT dependent, with southward IMF Bz causing geoeffective eastward ionospheric electric fields on the dayside and westward on the nightside (Tsurutani et al, 2004b.…”
Section: Discussionmentioning
confidence: 96%
“…During large magnetic storms PPEF can penetrate into the ionosphere for hours (Huang et al, 2005). Observations during moderate geomagnetic activity indicate that penetration can take place for ∼one hour (see Fejer, 2011, and references therein). Verkhoglyadova et al (2011) estimated that geoeffective CIR/HSS can cause a moderate (up to 10 times lower than a superstorm) E y ∼ 5 mV m −1 with less than ∼1-2 h to create a response in the low-latitude ionosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The F region dynamo field is largely shorted through the E region during the day but becomes more important in the evening as the E region conductivity declines (e.g., Heelis et al, 1974;Heelis, 2004). The basic characteristics of zonal plasma drift at the equator have been presented by Fejer et al (1981Fejer et al ( , 1985 and Fejer (2011) using Jicamarca data. A typical diurnal cycle consists of westward drifts of about 50 m s −1 during the day that are solar cycle independent and solar-cycle-dependent nighttime eastward drifts that peak pre-midnight with an average value of around 130 m s −1 .…”
Section: Introductionmentioning
confidence: 99%